منهجية الرازي عند إيراده للشواهد الشعرية النحوية في كتاب مفاتيح الغيب - Elsayed Mohamed Salem, Salem Elawadi; Hussein Ali Abdullah, Al-Thulaia; Khalid, Duhmah (2020)
Undoubtedly ،poetic verses that support grammatical usages have paramount significance in the explanation and preservation of the Gracious Quran and its linguistic integrity. Therefore ، Quran exegetes have been generally keen to collect poetry and quote relevant verses in support of the opinions and rules they adopted. Going through Mafateeh al-Ghayb ، one will come up with such distinguishing characteristics that make it a true masterpiece of genuine exegesis. It is distinguished with various quoted poetic verses that suit relevant subjects. Al-Razi has a special methodology in quoting these poetic verses as evidences for grammatical usages. This paper aims to exhibit this methodology with its detailed procedures and steps as compared to other similar books of Quranic exegesis. The paper employs the analytical approach to explore this methodology in an attempt to reveal how successful was such a brilliant exegete in quoting supportive poetic verses and employing them in proper contexts to expound the meanings of Quranic verses and their implications.